Learn to code with JavaScript - Jones, Darren (SitePoint, 2021)
A hands-on, practical Introduction to coding! Do you want to learn to code? Perhaps you want to learn how to build the next social media sensation or blockbuster game? Or perhaps you just want to get some valuable coding experience under your belt? This easy-to-follow, practical, and fun guide is the perfect place to start on your coding journey. You'll be learning to program with JavaScript - the most popular programming language on Earth. And it runs in web browsers, making it particularly suited to creating web-based apps and games. But the principles and techniques that you'll learn will provide you with a foundation to go on and learn many other languages, too. You'll learn: Programming basics, including data types, variables and more How to use logic to control the flow of a program How to use loops to repeat code over and over again How to write functions that can be used to store code in reusable blocks How to store data in collections such as arrays, sets and maps How to create objects that store properties and actions And much more! Along the way, you'll build a collection of fun applications, including games and interactive web pages. Start learning to code today!
Keywords: JavaScript (Computer program language); JavaScript (Langage de programmation)